Outdoor Learning; Numbered Head Implementasi Outdoor Learning Model Numbered Head Together dalam Meningkatkan Materi Keliling dan Luas Lingkaran - Wahyu, Lilik; Kunti Dian Ayu Afiani; Deni Adi Putra (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Satya Wacana, 2024)
This study aims to describe the implementation of Outdoor Learning using the NumberedHead Together (NHT) model, which can enhance students’ mathematics learningoutcomes on circumference and area of a circle, and to describe the results of students inthe learning process. The research is a Classroom Action Research (CAR) that carriedout in two cycles. Each cycle consists of planning, implementation, observation, andreflection. The research subjects were fourth grade students at SD Muhammadiyah 16Surabaya. The data collection techniques were observation and written tests, while the data analysis techniques involved the results of observation and simple statistics. Thefindings showed that in Cycle I, students’ achievement outcomes reached 62% with anaverage class of 77.75, and increased in Cycle II that reached 85% with an average classof 81.46. Based on the results of the completion and average class scores obtained, it can be concluded that the implementation of Outdoor Learning with the Numbered Head Together (NHT) model is said to be successful if the completion and average class scores increase significantly and make students become more active in discussing with each other to solve problems and understand the material.